2013
DOI: 10.1007/s11250-013-0438-8
|View full text |Cite
|
Sign up to set email alerts
|

The application of bioelectrical impedance analysis in live tropical hair sheep as a predictor of body composition upon slaughter

Abstract: Animal management for breeding and marketing can be improved by precise measurement of desirable traits. Live animal body composition analysis facilitates the selection of animals that are best suited for the intended purpose. This study was designed to assess the accuracy of bioelectrical impedance analysis (BIA) predicted live body tissue composition, as a proxy for the estimation of carcass quality in Barbados Black Belly lambs. Thirty-four Barbados Black Belly lambs were placed on an 8-week feeding regime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The bioimpedance technique, when used to evaluate the quality of the body composition of cattle, swine, sheep, buffaloes and rabbits, showed that the characteristics of the carcass, morphology, electrode positioning, and homogeneity of the parameters directly influenced the measurements (Altmann et al, 2004;Avril et al, 2013;Schäff et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bioimpedance technique, when used to evaluate the quality of the body composition of cattle, swine, sheep, buffaloes and rabbits, showed that the characteristics of the carcass, morphology, electrode positioning, and homogeneity of the parameters directly influenced the measurements (Altmann et al, 2004;Avril et al, 2013;Schäff et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Muscle tissues and proteins are considered electrical conductors and can measure conductance (C). That is, they have low electrical resistance (Avril et al, 2013). On the other hand, Mabrook & Petty (2003) demonstrated that milk lactose has little effect on electrical conductivity (EC), whereas the presence of fat results in a decrease in milk conductance.…”
Section: Introductionmentioning
confidence: 99%
“…The same applies to lean tissues formed by muscles and viscera, which are good conductors of ionic current due to their large amount of water and electrolytes. Adipose and bone tissues, on the other hand, conduct ionic current with less intensity, when compared to the muscles and viscera, being highly resistant (16) .…”
Section: Electric Bioimpedancementioning
confidence: 99%
“…The evaluation of the body composition is frequently used to improve management and zootechnical control on farm animal sector, enabling the responsible technician and raiser to select animals with higher performances, adapting them for the consuming market (16) . The most commonly used methods to predict the composition and the carcass of living or slaughtered animals are often time-consuming, expensive and invasive (10) .…”
Section: Bia For Body Composition and Carcasses Evaluation Of Farm Animalsmentioning
confidence: 99%
“…In vivo bioimpedance analysis (BIA) is a simple, rapid, relatively cheap, non-destructive, and minimally invasive method to estimate the body composition of sheep (Altmann, Pliquett, Suess, & Von Borell, 2004;Avril, Lallo, Mlambo, & Bourne, 2013;Berg & Marchello, 1994). Bioimpedance measures both modulus and phase of an equivalent impedance at a certain frequency, which is then calculated both resistance and reactance.…”
Section: Introductionmentioning
confidence: 99%